Malawi Summary of Baseline Studies: Country Report for the GFCS Adaptation Program in Africa - Tall, Arame; Kaur, Harneet; Hansen, James; Halperin, Mea (2015)
This report reflects the summary of baseline findings in Malawi, under the auspices of the Global Framework for Climate Services (GFCS) Adaptation Programme in Africa. It identifies gaps in climate information access and use at the local level, types of climate services farmers and pastoralists need in Malawi, relevant channels to reach farmers with requested services, lead-time and gender-specific requirements for the design and delivery of climate services that matter to farmers.